Correlation between histological type and immunohistochemical profile of prostate cancer and Gleason scale gradation - Iemelynova, A.A.; Grygorenko, V.M.; Cheremuha, S.V.; Romanenko, A.M. (Experimental Oncology, 2009)
Aim: To evaluate the characteristics of prostate cancer (PC) morphogenesis, taking into consideration the role of proliferation and apoptosis in tumor cells. Methods: р53, р16INK4a, Bcl-2 and Ki-67 proteins expression was analyzed by immunohistochemistry in paraffin embedded sections of biopsy specimens from PC patients. The level of tissue immunoreactivity was evaluated by semi-quantitative method with estimation of 100% colored cells content over 1000 cells in one specimen. Patients were divided into three groups in accordance to Gleason scale gradation: group 1 — with Gleason scale 5 and 8 (n = 6). Results: Upon histological examination of prostate biopsy specimens, it was found that in the first group in 6 out of 13 (46%) cases small acinic cell PC developed on the background of chronic prostatitis with РІА (proliferative inflammatory atrophy) locus, frequently in combination with prostatic intraepithelial neoplasia (РІN) locus. Hyperchromic epithelial cells in PIA locus were characterized by nuclear expression of р53 and Кі-67 proteins, and cytoplasmic expression of Bcl-2. The precancerous foci in the PIN and PIA in the biopsy specimens of the second group of PC patients were found in 2 out of 8 (25%) cases of large and small acinic cell adenocarcinoma observations. The expression level of р53, р16INK4a, Bcl-2 proteins and especially Кі-67 protein adequately increased in tumors of group 2 in comparison with group 1. Group 3 comprised of patients with Gleason scale > 8, predominantly solid structures or scirrhus of PC, which were characte rized by the highest nuclear expression of р53, р16INK4a and Кi-67, and also by overexpression of cytoplasmic Bcl-2. Conclusions: Obtained results showed the direct correlation between patients’ Gleason scale, and the expression level of р53, р16INK4a, Bcl-2 proteins and, particularly, Кі-67 marker of proliferating cells in PC tumor cells.